2013
DOI: 10.4236/ojvm.2013.36043
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Gastrointestinal Parasites of Horses and Donkeys in and around Gondar Town, Ethiopia

Abstract: A cross sectional study was conducted from October 2010 to June 2011 in and around Gondar town to identify the species and determine prevalence of gastrointestinal parasites in donkeys and horses. Gross examination, direct fecal smear, sedimentation and floatation techniques were utilized to identify the eggs and larvae of parasites in feces. A total of 384 horses and donkeys were examined for gastrointestinal parasites. The overall prevalence of gastrointestinal parasites was 92.71% (356 from 384) with 80.95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

20
34
24

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(79 citation statements)
references
References 8 publications
20
34
24
Order By: Relevance
“…To this, we observed a higher prevalence of babesiosis and helminthoses in adult horses and a higher prevalence of tick infestation in young horses. In line with our findings, Turaki et al (2014) and Mezgebu et al (2013) reported higher prevalence of babesiosis and helminthoses in adult horses in their work conducted in Nigeria and Ethiopia respectively. Interestingly, Enigidaw et al (2015) and Oladipo et al (2015) documented contrary to our findings.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…To this, we observed a higher prevalence of babesiosis and helminthoses in adult horses and a higher prevalence of tick infestation in young horses. In line with our findings, Turaki et al (2014) and Mezgebu et al (2013) reported higher prevalence of babesiosis and helminthoses in adult horses in their work conducted in Nigeria and Ethiopia respectively. Interestingly, Enigidaw et al (2015) and Oladipo et al (2015) documented contrary to our findings.…”
Section: Discussionsupporting
confidence: 82%
“…The higher prevalence of helminthoses in male compared to female horses we reported may be attributed to hormonal factors that results in debilitating immune functions, which favors the growth and spread of helminth parasites in male guts (Apio et al, 2006). Mezgebu et al (2013) reported a similar finding to ours in terms of helminth infections and sex. The prevalence of tick infestation is influenced by the origin of the horse, age, body condition, breed, climate conditions and colour among other factors (Osman et al, 2006;Payne et al, 2017) and this may have resulted in the high prevalence we recorded in female horses as against male.…”
Section: Discussionsupporting
confidence: 78%
“…Though the prevalence was higher in females than males the difference was not statistically significant (p > 0.05) and this agrees with the work of Fikru et al [16], Mezgebu et al [20], Berhanu et al [18], Tesfu et al [23] and Belay et al [24] who similarly reported non-significant difference. There was decrease in the prevalence of GIT helminthosis as the animals gets older and the prevalence was higher in young equines (71.4%) while the prevalence in adults and old equines was 40% and 32.9% respectively.…”
Section: Discussionsupporting
confidence: 81%
“…The prevalence of P. equorum was 8.3% which is in agreement with the study in Khartoum Sudan by Seri et al [30]. Prevalence of P. equorum in Ethiopia by Ayele et al [13], Fikru et al [16], Gizachew et al [17] and Mezgebu et al [20] was 50%, 17.1%, 50% and 66.67% respectively. Significant difference in the prevalence of P. equorum between age groups was reported by Zerihun [33] and Gebreab [34] in different areas of Ethiopia.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation